2010
DOI: 10.1149/1.3298891
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metallic Fe and Carbon Matrix in Fe[sub 2]O[sub 3]/Fe/Carbon Nanocomposite for Lithium-Ion Batteries

Abstract: A comparative study is made on the cycle and rate performance of three Fe 2 O 3 -containing electrodes. The first electrode is made from a commercial nanosized ͑Ͻ100 nm͒ Fe 2 O 3 powder, whereas the second is made from a carbon-supported nanosized Fe 2 O 3 ͑Fe 2 O 3 /carbon composite͒. The third electrode is prepared by modifying the second, incorporating the metallic Fe into the Fe 2 O 3 particles ͑Fe 2 O 3 /Fe/carbon composite͒. Three electrodes show the following performance order in the cycle retention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 31 publications
7
45
0
Order By: Relevance
“…1a-iii), in addition to the pristine support peaks. This diffraction peak was well matched with that for the metallic Fe, 29 indicating that, during the reduction process, Fe 2 O 3 particles reduced to the metallic state. The literature 13,23 also states that Fe 2 O 3 should convert to metallic Fe to serve as seeds for the growth of CNTs under CVD, which was consistent with the WAXS pattern observed in this work.…”
Section: Structural Properties Of the Catalystssupporting
confidence: 63%
See 1 more Smart Citation
“…1a-iii), in addition to the pristine support peaks. This diffraction peak was well matched with that for the metallic Fe, 29 indicating that, during the reduction process, Fe 2 O 3 particles reduced to the metallic state. The literature 13,23 also states that Fe 2 O 3 should convert to metallic Fe to serve as seeds for the growth of CNTs under CVD, which was consistent with the WAXS pattern observed in this work.…”
Section: Structural Properties Of the Catalystssupporting
confidence: 63%
“…The other diffraction peaks in this sample had been indexed with Fe 2 O 3 . 29 This showed that, during the calcination process, Fe 3+ ions, which intercalated into the layers of montmorillonite by wet impregnation with the Fe (NO 3 ) 3 solution, changed to Fe 2 O 3 . 13 The reduced support gave the most intense diffraction peak at 44.7° (Fig.…”
Section: Structural Properties Of the Catalystsmentioning
confidence: 96%
“…It is generally known that smallsized nanoparticles deposited on carbon materials such as rGO provide high specific surface area and fast redox reactions, which can reduce the charge transfer resistance [47].…”
Section: Electrochemical Performance Fe@agnps-aetrgo In Libmentioning
confidence: 99%
“…5c shows that there are two types of lattice fringes with lattice spacing of 0.202 and 0.252nm, correspond to the (110) planes of the Fe and the (311) planes of the Fe 3 O 4 ,respectively. Recently, Fe-doped ion oxide materials have been explored by physical mixture or thermal reduction of ion oxide for lithium storage, which showed better cycle performance than pure ion oxide[31]. The inactive Fe functionalities can reduce the electrode swelling during lithium insertion/desertion process.…”
mentioning
confidence: 99%
“…The inactive Fe functionalities can reduce the electrode swelling during lithium insertion/desertion process. In addition, considering the high electric conductivity of metallic Fe, the trace Fe in Fe 3 O 4 /Fe/MBCFs can also reduce the internal resistance and enhancing the rate capacity[31,32].…”
mentioning
confidence: 99%